Efficient detection of African Swine Fever Virus using minimal equipment through a LAMP PCR method - Bohorquez, Jose Alejandro; Lanka, Saraswathi; Rosell, Rosa; Pérez-Simó, Marta; Alberch, Mònica; Rodriguez, Fernando; Ganges, Llilianne; Maddox, Carol W. (Frontiers in Cellular and Infection Microbiology, 2023)
African swine fever virus (ASFV) currently represents the biggest threat to the porcine industry worldwide, with high economic impact and severe animal health and welfare concerns. Outbreaks have occurred in Europe and Asia since ASFV was reintroduced into the continent in 2007 and, in 2021, ASFV was detected in the Caribbean, raising alarm about the reemergence of the virus in the Americas. Given the lack of vaccines against ASFV, control of the virus relies on molecular surveillance, which can be delayed due to the need for sample shipment to specialized laboratories. Isothermal PCR techniques, such as LAMP, have become increasingly attractive as point-of-care diagnostic tools given the minimal material expense, equipment, and training required. The present study aimed to develop a LAMP assay for the detection of ASFV. Four LAMP primer sets were designed, based on a consensus sequence for the ASFV p72 gene, and were tested using a synthetic plasmid containing the cloned ASFV p72 target gene as a positive control. Two primer sets, were selected for further validation, given their very short time for amplification. Both primer sets showed thermal stability, amplifying the ASFV DNA at temperatures between 60-70°C and proved to have an analytical limit of detection as low as one ASFV-plasmid DNA copy/µL, using both fluorometric and colorimetric methods. They also showed high specificity. Testing of DNA-spiked samples showed that LAMP amplification was not affected by the nature of the matrices, including oral fluids, tonsils, blood, or rectal swabs. The primer sets were able to detect the two more prevalent ASFV genotypes (I&II) in the field. Taken together, the results show that ASFV-LAMP-BG2 and ASFV-LAMP-BG3 would be a useful tool for rapid, highly sensitive on-site diagnostic testing.